2013
DOI: 10.4110/in.2013.13.2.70
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Is an Essential Factor on the Anti-viral Immune Responses through the Production of Interferon-α/β at the Initial Stage of Influenza A Virus (H3N2) Infection

Abstract: L-ascorbic acid (vitamin C) is one of the well-known anti-viral agents, especially to influenza virus. Since the in vivo anti-viral effect is still controversial, we investigated whether vitamin C could regulate influenza virus infection in vivo by using Gulo (-/-) mice, which cannot synthesize vitamin C like humans. First, we found that vitamin C-insufficient Gulo (-/-) mice expired within 1 week after intranasal inoculation of influenza virus (H3N2/Hongkong). Viral titers in the lung of vitamin C-insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
159
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(163 citation statements)
references
References 17 publications
2
159
0
2
Order By: Relevance
“…In contrast, on late stages the levels of RANTES, MCP-1 and IL-12 were lower than in control mice [38]. In another similar study [36], it was shown that viral activity in the lung tissue of Gulo (-/-) mice was increased in the absence of AA, and the production of the antiviral cytokine IFNα/β was lower than in animals receiving AA. The level of cellular infiltration and the production of pro-inflammatory cytokines, such as TNFα and IL-1α/β in lung tissue, were increased.…”
Section: Figure Ascorbic Acidmentioning
confidence: 78%
“…In contrast, on late stages the levels of RANTES, MCP-1 and IL-12 were lower than in control mice [38]. In another similar study [36], it was shown that viral activity in the lung tissue of Gulo (-/-) mice was increased in the absence of AA, and the production of the antiviral cytokine IFNα/β was lower than in animals receiving AA. The level of cellular infiltration and the production of pro-inflammatory cytokines, such as TNFα and IL-1α/β in lung tissue, were increased.…”
Section: Figure Ascorbic Acidmentioning
confidence: 78%
“…The neutrophil phagocytic activity and oxidative death were also enhanced [95][96][97]. Lymphocyte proliferation was also accelerated [95][96][97].…”
Section: Treatment Of Viral Infectionsmentioning
confidence: 97%
“…In general, Ascorbic acid is concentrated in leucocytes, lymphocytes, and macrophages [93,94]. Chemotaxis was improved by Vit-C [95][96][97]. The neutrophil phagocytic activity and oxidative death were also enhanced [95][96][97].…”
Section: Treatment Of Viral Infectionsmentioning
confidence: 99%
“…Thus, Gulo -/ -mice are useful to investigate the in vivo effect of vitamin C because they are unable to synthesize vitamin C and exhibit physiological responses that resemble those in vitamin C-deficient humans. We have recently reported on the regulatory role of vitamin C in the inflammation of the liver and heart, as well as on the viral infection of vitamin C-deficient Gulo -/ -mice (2,25,29). We have also found a preferential accumulation and maintenance of vitamin C in the brain.…”
Section: Discussionmentioning
confidence: 85%